Study on using fatty acid data in the botanical chemotaxonomy for Vietnamese seaweed species - Thanh, Le Tat; Hue, Pham Thu; Anh, Nguyen Van Tuyen; Tien, Dam Duc (Vietnam Journal of Biotechnology, 2021)
Vietnam’s sea is assessed to be very diverse and rich in seaweed species. It is about 1000 different species of seaweed, of which more than 800 species have been identified, classify into genus, families, classes, phylums, and continuously updated from the 1950s to the present. Previous studies by Vietnamese and international scientists have shown that lipids from seaweed contain many valuable active ingredients such as acids C20: 4n-6 (AA), C20:5n-3 (EPA), C22:6n-3 (DHA), prostaglandin E2… In this study, fatty acids were converted to methyl esters and identified by gas chromatography using flame ionization detector (GC-FID) with column Cap Mao Equity 5 (Merck, L×ID 30m×0.25 mm, df 0.25 µm). From the total lipid of 50 of Vietnamese seaweed, we have identified 30 fatty acids, in which, C16:0, C18:1n-9, C20:4n-6 (AA) fatty acids have the high content, and C20:5n-3 (EPA), C22:6n-3 (DHA), C22:5n-3 (DPA) fatty acids have the high bioactivities. By the method of PCA main component analysis, from the dataset of fatty acids, we have identified 8 main fatty acids with high correlation and used to represent the distribution of seaweed species on the two-way plane. Three phylums were classified by different fatty acid groups with the high reliability. In the detail, the distribution of the phylum Phaeophyta depends on the content of 3 fatty acids including C16:1n-7, C18:1n-9 và C20:4n-6, the phylum Rhodophyta depends on C15:0, C16:0, C18:0 fatty acids, and the phylum Chlorophyta depends on C18:1n-7, C18:3n-6 fatty acids. This method can may help provides more chemical data in the taxonomy of Vietnamese seaweed species.